Premedication before laryngoscopy in neonates: Evidence-based statement from the French society of neonatology (SFN) - Durrmeyer, Xavier; Walter-Nicolet, Elizabeth; Chollat, Clément; Chabernaud, Jean-Louis; Barois, Juliette; Chary Tardy, Anne-Cécile; Berenguer, Daniel; Bedu, Antoine; Zayat, Noura; Roué, Jean-Michel; Beissel, Anne; Bellanger, Claire; et al. (Frontiers in Pediatrics, 2023)
Context: Laryngoscopy is frequently required in neonatal intensive care. Awake laryngoscopy has deleterious effects but practice remains heterogeneous regarding premedication use. The goal of this statement was to provide evidence-based good practice guidance for clinicians regarding premedication before tracheal intubation, less invasive surfactant administration (LISA) and laryngeal mask insertion in neonates. Methods: A group of experts brought together by the French Society of Neonatology (SFN) addressed 4 fields related to premedication before upper airway access in neonates: 1) tracheal intubation; 2) less invasive surfactant administration; 3) laryngeal mask insertion; 4) use of atropine for the 3 previous procedures. Evidence was gathered and assessed on predefined questions related to these fields. Consensual statements were issued using the GRADE methodology. Results: Among the 15 formalized good practice statements, 2 were strong recommendations to do (Grade 1+) or not to do (Grade 1-), and 4 were discretionary recommendations to do (Grade 2+). For 9 good practice statements, the GRADE method could not be applied, resulting in an expert opinion. For tracheal intubation premedication was considered mandatory except for life-threatening situations (Grade 1+). Recommended premedications were a combination of opioid + muscle blocker (Grade 2+) or propofol in the absence of hemodynamic compromise or hypotension (Grade 2+) while the use of a sole opioid was discouraged (Grade 1-). Statements regarding other molecules before tracheal intubation were expert opinions. For LISA premedication was recommended (Grade 2+) with the use of propofol (Grade 2+). Statements regarding other molecules before LISA were expert opinions. For laryngeal mask insertion and atropine use, no specific data was found and expert opinions were provided. Conclusion: This statement should help clinical decision regarding premedication before neonatal upper airway access and favor standardization of practices.